Multiplanetary Imaginaries and Utopia: The Case of Mars One - Tutton, Richard (Science, technology, & human values, 2018)
The prospect of human societies being made anew on other planets is a powerful recurring theme in popular culture and speculative technoscience. I explore what Science and Technology Studies (STS) offers to analyzing how the future is made and contested in present-day endeavors to establish humans as multiplanetary subjects. I focus on the case of Mars One—an initiative that aims to establish a human settlement on Mars in the 2020s—and discuss interviews undertaken with some of the individuals who have volunteered to be the first humans to live on Mars, drawing on STS work on futures and sociotechnical imaginaries and scholarly discussions of utopia. Seeing themselves as part of a project that would start to “establish what it means to live on another planet,” I discuss how interviewees talked about how sociotechnical relations could be remade in the future, both on Earth and on Mars, through the pursuit of this technoscientific project. I conclude that this project is an expression of a multiplanetary imaginary of human beings no longer subject to Earth—but, through sociotechnical inventiveness, able to live on other planets.